Optical Fiber Integrated Functional Micro-/Nanostructure Induced by Two-Photon Polymerization - Xiong, Cong; Liao, Changrui; Li, Zhengyong; Yang, Kaiming; Zhu, Meng; Zhao, Yuanyuan; Wang, Yiping (Frontiers in Materials, 2020)
Owing to the limitation of optical fiber materials and conventional fabrication methods, the development of optical fiber devices has encountered a bottleneck. Recently, two-photon polymerization technology are attracting increasing research interest due to its superiorities of high precision, flexibility and diversity of polymer materials. The optical fiber integrated micro-/nanostructures realized by two-photon polymerization have become a research hotspot due to the great application expansion of optical fiber device. In this paper, we review the research progress in the field of optical fiber integrated micro-/nanostructure induced by two-photon polymerization in the last ten years, which are classified by micro-optics, optical waveguide device and optical micro-cavity. Furthermore, we briefly discussed the future prospects of this exciting research field.